Modifying Alexithymia by Implementing Emotional Regulation Skills among Anxious Students - Agahheris, Mojgan (International Journal of Applied Behavioral Sciences, 2017)
Objective: The main purpose of this study was modifying anxiety and alexithymia by instructing emotional regulation skills among anxious female students in Tehran. Method: Quasi-experimental design was applied in this study. Convenient sampling method with 50 volunteer female high school students was utilized. Their scores ranged from 26-36 in Beck anxiety questionnaire and eligible to exclude- include criteria were selected and participants were randomly assigned into two experimental, and control group (each group included 25 subjects). Results: Data analysis and applying ANCOVA methods revealed the instructing emotional regulation skills could significantly decrease anxiety, and alexithymia among subjects in experimental in comparison to subjects in control group (P<0.05). Conclusion: Implementing cognitive and emotional regulation skills such as restructuring of content and process of sabotaging beliefs, modifying negative emotions, using reappraisal, reinterpretation, problem solving, mindfulness techniques, and emotional regulation could reduce anxiety and alexithymia symptoms in anxious students.